Brief heat training: No improvement of the lactate threshold in mild conditions - Chalmers, S.; Esterman, A.; Eston, R.; Norton, K. (International Journal of Sports Physiology and Performance, 2016)
Purpose: Athletes often seek the minimum required time that might elicit a physiological or performance change. It is reasonable to suggest that heat training may improve aerobic-based performance in mild conditions. Therefore, rather than providing a traditional heat-exposure stimulus (ie, 7-10 × 60-100 min sessions), the current article details 2 studies that aimed to determine the effect of brief (=240 min exposure) heat training on the second lactate threshold (LT2) in mild conditions.